PREVALENCE OF (Aspergillus niger) IN OTOMYCOSIS AT PROF. DR. MARGONO SOEKARJO HOSPITAL - Dinda Victoria; Anriani Puspita Karunia Ning Widhi; Darmawan Anton Budhi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2023)
Otomycosis is a chronic fungal infection with high prevalence. Environmental factors dan predisposing factors can influence a patient’s vulnerability to otomycosis. According to studies conducted in several country, Aspergillus niger is the common fungus that causes otomycosis. This study aims to determine the prevalence of Aspergillus niger in patients at Prof. dr. Margono Soekarjo Hospital, who was clinically diagnosed with otomycosis. The study was done at the ENT Poly of Prof. dr. Margono Soekarjo Hospital and Microbiology Laboratory of Medicine Faculty, Jenderal Soedirman University between August 2022 to Januari 2023 as a descriptive observational study. According to the inclusion criteria, there were 42 subjects and 46 samples that ENT specialists carried out with sterile flocked swabs, the isolated the samples bedside on SDA Chloramphenicol, Czapek Dox agar, and object glass. Samples were observed macroscopically and microscopically with 10% KOH and LPCB staining. Patients with Aspergillus niger infection in otomycosis at Prof. dr. Margono Soekarjo Hospital , are represented by nine (19,56%) out of the 46 samples. The gender with the highest sex precentage is female (55,56%), folllowed by the age range of 26 – 35 years (44,45%). The prevalence of Aspergillus niger as a cause of otomycosis in Prof. dr. Margono Soekarjo Hospital is 19,56%, the most in females and the age group 26 – 35 years.